Exceptional hydrogen permeation of all-ceramic composite robust membranes based on BaCe0.65Zr0.20Y0.15O3−δ and Y- or Gd-doped ceria. Issue 12 (26th October 2015) - Rebollo, Elena; Mortalò, Cecilia; Escolástico, Sonia; Boldrini, Stefano; Barison, Simona; Serra, José M.; Fabrizio, Monica
Abstract : Mixed proton and electron conductor ceramic composites were examined as hydrogen separation membranes at moderate temperatures (higher than 500 °C). Abstract : Mixed proton and electron conductor ceramic composites were examined as hydrogen separation membranes at moderate temperatures (higher than 500 °C). In particular, dense ceramic composites of BaCe0.65 Zr0.20 Y0.15 O3− δ (BCZ20Y15) and Ce0.85 M0.15 O2− δ (M = Y and Gd, hereafter referred to as YDC15 and GDC15), as protonic and electronic conducting phases respectively, were successfully prepared and tested as hydrogen separation membranes. The mixture of these oxides improved both chemical and mechanical stability and increased the electronic conductivity in dual-phase ceramic membranes. The synthetic method and sintering conditions were optimized to obtain dense and crack free symmetric membranes. The addition of ZnO as a sintering aid allowed achieving robust and dense composites with homogeneous grain distribution. The chemical compatibility between the precursors and the influence of membrane composition on electrical properties and H2 permeability performances were thoroughly investigated. The highest permeation flux was attained for the 50 : 50 volume ratio BCZ20Y15–GDC15 membrane when the feed and the sweep sides of the membrane were hydrated, reaching values of 0.27 mL min −1 cm −2 at 755 °C on a 0.65 mm thick membrane sample, currently one of the highest H2 fluxes obtained for bulk mixed protonic–electronic membranes. Increasing the temperature to 1040 °C, increased the hydrogen flux up to 2.40 mL min −1 cm −2 when only the sweep side was hydrated. The H2 separation process is attributed to two cooperative mechanisms, i.e. proton transport through the membrane and H2 production via the water splitting reaction coupled with oxygen ion transport. Moreover, these composite systems demonstrated a very good chemical stability under a CO2 -rich atmosphere such as catalytic reactors for hydrogen generation.